The anatomy of citizen science projects in information systems - Dang, Duong; Mäenpää, Teemu; Mäkipää, Juho-Pekka; Pasanen, Tomi (University of Illinois at Chicago Library, 2022)
Citizen science is an emerging approach for conducting research in the field of information systems. It refers to the participation of individuals with various backgrounds in research projects. It is necessary to match research implementation closely with plans because the anatomy of a citizen science project is quite complex. The literature shows that managing a long-term citizen science project is an even more complex task. To obtain a coherent understanding of citizen science in the field of information systems, we conducted a systematic literature review on the topic for which we used all the major information systems journals and conference proceedings. We devised the episode framework which consists of four blocks: design of pillars, the episodes of CS implementation, adjustment of activities, and post-implementation. The framework emphasizes the Weinhardt division of the project into separate episodes which are sequentially ordered but which we need to run in parallel because of the dynamic nature of a citizen science project when participants can join and leave freely. Moreover, in some projects, participants can take on different roles, which complicates project management further.
Keywords: information systems; citizen science; fi=Tietotekniikka|en=Computer Science|